Vascular endothelial‐cadherin stimulates syndecan‐1‐coupled insulin‐like growth factor‐1 receptor and cross‐talk between αVβ3 integrin and vascular endothelial growth factor receptor 2 at the onset of endothelial cell dissemination during angiogenesis - Rapraeger, Alan C.; Ell, Brian J.; Roy, Madhuchhanda; Li, Xuehui; Morrison, Orrianne R.; Thomas, Grant M.; Beauvais, DeannaLee M. (The FEBS journal, 2013)
Vascular endothelial growth factor (VEGF)‐stimulated angiogenesis depends on a cross‐talk mechanism involving VEGF receptor 2 (VEGFR2), vascular endothelial (VE)‐cadherin and the αVβ3 integrin. Because we have shown that αVβ3 integrin activation is dependent on its incorporation, along with the insulin‐like growth factor‐1 receptor (IGF1R) kinase, into a ternary receptor complex organized by the matrix receptor syndecan‐1 (Sdc1), we questioned the role of this core complex in VEGF‐stimulated angiogenesis. We find that the Sdc1‐coupled ternary receptor complex is required for VEGF signalling and for stimulation of vascular endothelial cell migration by vascular endothelial cadherin (VE‐cadherin) engagement. VE‐cadherin binding to Fc/VE‐cadherin extracellular domain chimera activates Sdc1‐coupled IGF1R and αvβ3 integrin; this depends on VEGFR2 and c‐Src activated by the cadherin. Blocking homotypic VE‐cadherin engagement disrupts VEGF‐stimulated cell migration, which is restored by clustering the cadherin in the absence of cell–cell adhesion. This cadherin‐dependent stimulation requires VEGFR2 and IGF1R and is blocked by synstatin (SSTN)92–119, a peptide that competitively disrupts the Sdc1‐coupled ternary complex and prevents the αVβ3 integrin activation required for VEGFR2 activation. VEGFR2‐stimulated angiogenesis in the mouse aortic ring explant assay is disrupted by SSTN, although only early in the process, suggesting that IGF1R coupling to Sdc1 and αVβ3 integrin comprises a core activation mechanism activated by VE‐cadherin that is necessary for VEGFR2 and integrin activation in the initial stages of endothelial cell dissemination during angiogenesis. The αVβ3 integrin is captured with the insulin‐like growth factor‐1 receptor (IGF1R) by the matrix receptor syndecan‐1 (Sdc1). This core receptor complex is required for angiogenesis stimulated by VEGF and VE‐cadherin. Disruption of the Sdc1‐coupled complex by synstatin prevents activation of VEGFR2 by VEGF or by homophillic VE‐cadherin engagement and prevents the initial phase of endothelial cell dissemination during angiogenesis.